Associations between Carotid Artery Wall Thickness and Cardiovascular Risk Factors Using Multidetector CT - Saba, L.; Sanfilippo, R.; Montisci, R.; Mallarini, G. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: It has been demonstrated that the increase in CAWT is associated with an increased risk of stroke and its severity. The aim of this study was to determine whether CAWT evaluated by MDCTA is associated with the following cardiovascular risk factors: hypertension, diabetes mellitus, dyslipidemia, and smoking. MATERIALS AND METHODS: This was a retrospective study. One hundred sixty-eight patients (120 men; mean age, 68.96 years ± 11.2 years SD) were analyzed by using a multidetector row CT scanner. In each patient, CAWT was measured by using an internal digital caliper. Continuous data were described as the mean value ± SD and were compared by using the Student t test. We performed simple logistic regressions to evaluate the association between CAWT and the following: hypertension, diabetes mellitus, dyslipidemia, and smoking. A P value < .05 indicated statistical significance. RESULTS: The distal common CAWT varied from 0.5 to 1.5 mm. We observed that hypertension and diabetes mellitus were associated with increased (>1 mm) CAWT (P = .0041 and P = .0172, respectively). There was no significant association between increased CAWT and dyslipidemia or smoking. CONCLUSIONS: In our selected group, the results of this work show that an increased CAWT is associated with the cardiovascular risk determinants hypertension and diabetes. Further studies are necessary to evaluate whether it is possible to apply our observations to the general population. Azarea under each ROC curveCAWTcarotid artery wall thicknessCCA-IMTcommon carotid artery intima-media thicknessCIconfidence intervalCTACT angiographyIMTintima-media thickness+LRXXX−LRXXXMDCTAmultidetector row CTANCnot calculableROCreceiver operating characteristic analysisStd.standardTIAtransient ischemic attack